If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 4)(3x + -15) = 0 Reorder the terms: (4 + x)(3x + -15) = 0 Reorder the terms: (4 + x)(-15 + 3x) = 0 Multiply (4 + x) * (-15 + 3x) (4(-15 + 3x) + x(-15 + 3x)) = 0 ((-15 * 4 + 3x * 4) + x(-15 + 3x)) = 0 ((-60 + 12x) + x(-15 + 3x)) = 0 (-60 + 12x + (-15 * x + 3x * x)) = 0 (-60 + 12x + (-15x + 3x2)) = 0 Combine like terms: 12x + -15x = -3x (-60 + -3x + 3x2) = 0 Solving -60 + -3x + 3x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '3'. 3(-20 + -1x + x2) = 0 Factor a trinomial. 3((-4 + -1x)(5 + -1x)) = 0 Ignore the factor 3.Subproblem 1
Set the factor '(-4 + -1x)' equal to zero and attempt to solve: Simplifying -4 + -1x = 0 Solving -4 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + -1x = 0 + 4 Combine like terms: -4 + 4 = 0 0 + -1x = 0 + 4 -1x = 0 + 4 Combine like terms: 0 + 4 = 4 -1x = 4 Divide each side by '-1'. x = -4 Simplifying x = -4Subproblem 2
Set the factor '(5 + -1x)' equal to zero and attempt to solve: Simplifying 5 + -1x = 0 Solving 5 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -1x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -1x = 0 + -5 -1x = 0 + -5 Combine like terms: 0 + -5 = -5 -1x = -5 Divide each side by '-1'. x = 5 Simplifying x = 5Solution
x = {-4, 5}
| 4f=1/9 | | 41-5x=13x+19 | | 12+6*24+254-2*0= | | 2(x+6)/4=3x-5 | | 0.60x+0.60(40)=0.30(56) | | m=4m+4z | | 5x+2-6-10=x+520 | | -(1/15)b=5/6 | | s=4m+4zwhatm | | -16t^2+64t+28=0 | | -11p-5(2-3p)=2(p-2)-16 | | 93-5x=22x+15 | | (2x^5/3)^7/x^4/7 | | 14-9x=7x+16 | | 9x+25=3x+13 | | 0.7x-0.6x-4=2 | | 19x-1+2x+8=180 | | 5x+10=102+9x | | 5-13x=89 | | -10y=-3+10y | | 2/5-6/7y=-1/2 | | -313-7x=8x+19 | | 6(w+3)-(-7w-7)=12w | | X^3+4x-100=0 | | 3(x-5)=2x-8 | | -9x-13-9=-31 | | -2w+4(w-4)=-4 | | 8z+2-z=1+6z-7 | | 5y+4y=8y+8 | | 5/6=-(2/5)b+(1/3)b | | -32=6u+4(u+2) | | -20=6(v-7)+5v |